“Selfish, Short-Sighted, and Sanctimonious”: Bowdoin College, Alex Schulten, the 1.600 Rule and the Welch Scholarship - Covell, Dan (Journal of Intercollegiate Sport, 2012)
In this article, the author examines passage of the National Collegiate Athletic Association’s (NCAA) 1.600 Rule in 1965 and the ramifications of that mandate. In drawing from administrative letters and memoranda available through the George J. Mitchell Department of Special Collections and Archives, the author investigates Bowdoin College’s response to the 1.600 Rule, the influence of the College’s confrontation with the NCAA on its athletes and their ability to compete at the national level, and how the conflict shaped the institution’s operations. Ramifications for Bowdoin College and the NCAA are discussed.